THE PENGARUH MODEL GAME BASED LEARNING BERBANTUAN MEDIA JELAJAH TERHADAP PEMAHAMAN KONSEP DAN KOLABORASI SISWA KELAS IV SDN LEMAHIRENG 01 - Nita Ramadhani; Kartika Yuni Purwanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to determine the differences and the effects of the Game Based Learning (GBL) model assisted by JELAJAH media on students’ conceptual understanding and collaboration skills in grade IV of SDN Lemahireng 01. The problem underlying this research is the low level of students’ conceptual understanding and collaboration skills in IPAS learning, caused by teacher-centered learning models that do not actively engage students. This study employed a quantitative approach using a quasi-experimental method with a non-equivalent control group design. The research subjects consisted of two classes: class IV A as the control group and class IV B as the experimental group. Data were collected through conceptual understanding tests, collaboration skills questionnaires, and learning implementation observation sheets. The data were analyzed using an independent sample t-test and simple linear regression analysis. The results showed that there were differences in conceptual understanding and collaboration skills between students taught using the GBL model assisted by JELAJAH media and those taught using conventional learning. Furthermore, the regression analysis indicated that the GBL model assisted by JELAJAH media had a significant effect on improving students’ conceptual understanding and collaboration skills. Therefore, the GBL model assisted by JELAJAH media is effective in improving the quality of IPAS learning in elementary schools, particularly in enhancing students’ conceptual understanding and collaboration skills.